Opportunities For Cyber Notary Implementation In A Legal Perspective - Lili Julianti; Gunawan Djajaputra (Journal of Law, Politic and Humanities, 2024)
The capacity of notaries to provide top-notch services that are quick, strategic, and community-solving is crucial in this age of fast-paced technological, informational, and communicative advancements. The usage of a cyber notary is one strategy for delivering timely and strategic services to the public. To be clear, the power to certify electronically performed transactions is the only one that now exists under the umbrella of "cyber notary," which refers to a system that notaries may employ to carry out their responsibilities and exercise their authority via electronic institutions. In accordance with the explanation of Article 15 paragraph (3) of Law Number 2 of 2014 on Amendments to Law Number 30 of 2004 on the Position of Notary (UUJN), this article aims to shed light on the possible capabilities of cyber notaries. Using a statutory approach, this study applies normative legal theory. Both Article 77 of Law Number 40 of 2007 about Limited Liability Companies and Law Number 11 of 2008 concerning Electronic Information and Transactions (UU ITE) deal with the electronic preservation of notary protocols. The minutes of the annual meeting of shareholders prove that cyber notary prospects really exist. Due to the Notary Position Law's lack of explicit regulation of the chances for creating deeds using electronic media, the implementation of cyber notary currently faces hurdles.